PELATIHAN PENINGKATAN KUALITAS EVALUASI PEMBELAJARAN BAHASA ARAB BERBASIS INFORMATION DAN COMMUNICATION TECHNOLOGY (ICT) UNTUK PENGAJAR BAHASA ARAB - Fauzi, Moh. Fery; Fatoni, Ahmad; Anindiati, Irma (UNIVERSITAS PGRI MADIUN, 2020)
Abstract. Information and communication technology (ICT) have an important role in teaching and learning activities, especially in learning assessment. Instructional assessment is one of a series of learning activities aimed at correcting, controlling the extent to which learning objectives have been achieved. Instructional assessment can be done with the help of computers and the internet so that the management of learning outcomes becomes easier, faster, and real time. The technology that can be used in the assessment process is such as edmodo, google quiz, hot potatoes, quiz creator. But in reality, most learning activities that teachers use are still conventional. That is due to the lack of knowledge and mastery of teachers on the use of information and communication technology, especially in instructional assessment. Therefore, there is a need for training on the use of ICT-based Instructional assessment to improve teachers’ competency. The approach method used assistance that includes socialization, workshops, training, hands-on practice, and evaluation. The results obtained state that evaluation of learning is very important for a program and purpose, both educational, learning, or training programs.Abstrak. Teknologi informasi dan komunikasi memiliki peranan penting dalam kegiatan belajar mengajar terutama dalam evaluasi pembelajaran. evaluasi pembelajaran merupakan salah satu rangkaian dalam kegiatan pembelajaran yang bertujuan untuk mengoresksi, mengontrol sejauh mana tujuan pembelajaran telah dicapai. Evaluasi pembelajaran dapat dilakukan dengan bantuan komputer serta internet sehingga pengelolaan hasil belajar pun menjadi lebih mudah, cepat dan real time. Adapun teknologi yang dapat digunakan dalam proses evaluasi tersebut seperti edmodo, google quiz, hot potatoes, quiz creator. Akan tetapi realitanya, kebanyakan kegiatan pembelajaran yang digunakan guru sekarang masih konvensional. Hal itu disebabkan minimnya pengetahuan dan penguasaan guru terhadap pemanfaatan teknologi informasi dan komunikasi terutama dalam evaluasi pembelajaran. Oleh sebab itu perlu adanya pelatihan pemanfaatan evaluasi pembelajaran berbasis ICT meningkatkan kompetensi guru. Metode pendekatan yang digunakan adalah pendampingan yang meliputi sosialisasi, workshop, pelatihan, praktik langsung, dan evaluasi. Hasil yang didapatkan menyatakan bahwa evaluasi pembelajaran sangat penting untuk suatu program dan tujuan, baik program pendidikan, pembelajaran, atau pun pelatihan.